2017
DOI: 10.1051/matecconf/20179502009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of machining parameters on surface finish of Inconel 718 in end milling

Abstract: Abstract. Surface finish is an important criteria in machining process and selection of proper machining parameters is important to obtain good surface finish. In the present work effects of the machining parameters in end milling of Inconel 718 were investigated. Central composite design was used to design the total number of experiments. A Mathematical model for surface roughness has been developed using response surface methodology. In this study, the influence of cutting parameters such as cutting speed, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Li et al [167] determined in their work the optimal cutting speed when processing Inconel 718, at which there are no diffusion phenomena that contribute to the formation of cuts on the back surface and craters on the front surface. Nalbant et al [168] studied the wear mechanisms of SiAlON tools when machining a nickel alloy with plates having different geometric shapes (RNGN 120700, and SNGN 120712). Practice has shown that the predominant failures of square plates are crater wear along the front surface and mechanical wear along the rear surface, while for round plates, it is the formation of notches and mechanical wear on the rear surface.…”
Section: Sialon Application In Machining Nickel-based Alloysmentioning
confidence: 99%
“…Li et al [167] determined in their work the optimal cutting speed when processing Inconel 718, at which there are no diffusion phenomena that contribute to the formation of cuts on the back surface and craters on the front surface. Nalbant et al [168] studied the wear mechanisms of SiAlON tools when machining a nickel alloy with plates having different geometric shapes (RNGN 120700, and SNGN 120712). Practice has shown that the predominant failures of square plates are crater wear along the front surface and mechanical wear along the rear surface, while for round plates, it is the formation of notches and mechanical wear on the rear surface.…”
Section: Sialon Application In Machining Nickel-based Alloysmentioning
confidence: 99%
“…For designing the end milling experiments, three factors, namely, spindle speed, feed rate, and depth of cut [20], were considered three levels of each factor. e experimental design and parameters for the end milling process are shown in Table 3.…”
Section: Optimization Of End Milling Variablesmentioning
confidence: 99%
“…Sarkar et al studied the impact of machining parameters concerning the end milling process and the response variables, such as surface finish to be measured in the Inconel 718 material. e results show that the cut's depth significantly influences the surface roughness measurement for the milling operation [20]. Shihab et al studied the optimization of the end milling process on the aluminum 7075 metal matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…The surface roughness grows with increasing the feed speed, but cutting depth has more influence on surface quality in comparison to feed rate. [ 85 ] Kiswanto et al [ 86 ] explored the influence of machining constraints on the surface roughness in micro‐milling of Inconel 718. The results explored that increasing the feed rate provided high surface roughness.…”
Section: Machinabilitymentioning
confidence: 99%